Mechanisms of heteroresistance in methicillin-resistant Staphylococcus aureus. - Ryffel, C (1994)
Characteristic for methicillin-resistant (Mcr) staphylococci is the heterogeneous expression of the intrinsic methicillin resistance. The majority of the cells express resistance to low concentrations of methicillin, and a minority of the cells express resistance to much higher concentrations. We show here (i) that the presence of the mecA encoding region on plasmid pBBB79 was sufficient to render a methicillin-susceptible (Mcs) Staphylococcus aureus strain heteroresistant and (ii) that this Mcr strain segregated highly resistant subclones which retained the high-resistance phenotype under nonselective growth conditions. The Mcr strain with only mecA on plasmid pBBB79 thus behaved identically to a Mcr strain carrying the complete mec determinant integrated at its proper chromosomal site. (iii) Curing a such highly resistant subclone from plasmid pBBB79 yielded an Mcs strain that was as susceptible as the original Mcs parent strain. (iv) Comparisons were made between the original parent and the cured Mcs strain by backcrossing pBBB79 into them and looking at their progeny. Transductants derived from the formerly highly resistant cured strain became resistant to high concentrations of methicillin, whereas transductants derived from the original parent strain were resistant to lower concentrations of methicillin and showed the typical heterogeneous resistance. We deduced therefrom that the high-level resistance expressed by the minority of the population of Mcr S. aureus was due to a chromosomal mutation(s) (chr*) involving neither mecA nor the additional 30 kb of mec-associated DNA. Moreover, we could show that this postulated mutation chr* was not linked to the femAB operon, which is known to affect methicillin resistance levels.